EFEKTIVITAS PENGGUNAAN KOMIK BERBASIS SIKAP ILMIAH TERHADAP SIKAP PEDULI LINGKUNGAN MAHASISWA UNIVERSITAS SLAMET RIYADI - Wicaksono, Anggit Grahito; Widyaningrum, Ratna (Universitas Muhammadiyah Surakarta, 2017)
The purpose of this research is to know: (1) difference of environmental care attitude of students before and after using comic based scientific attitude on basic natural science subjects and (2) effectiveness of the use of comic based scientific attitudes toward environmental care attitude on basic natural science subjects. This research uses pre experimental quantitative research method with one group pretest-posttest design with t-test and N-gain test analysis technique. The results of the first hypothesis test concluded that there are differences in environmental cares attitude before and after using comic based scientific attitude and experienced an increase in average values of environmental care attitude before and after using comic based scientific attitude. The result of the second hypothesis test concludes that the use of comic based scientific attitude is effective on the environmental cares attitude of students on the medium criterion with the value of the N-gain test of 0.425.